Determinants of consumers’ choice of online merchant - Lim, Bee Khim; Vooi, Wen Yan (2019)
This research will study about the factors influencing the consumers’ choice of online merchants. Price, sales volume, stickiness to the website, website quality, order fulfilment, reputation and trust, ratings and reviews will influence the choice of online merchants. The study will also shows which e-commerce website is the most used by consumers and also which e-commerce website will be the most intended to use by the consumers in the future. In this study, 140 survey questionnaires was distributed to the respondents in the form of paper and also through online. Convenience and judgement sampling had been used in this research. The Cronbach’s Alpha Reliability test will also conducted in this research. Moreover, the findings, implication and also the limitation of study are discussed in the chapter 5.